2018
DOI: 10.1177/1533033818759878
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Factors Affecting Clinical Response and Short-Term Survival to Drug-Eluting Bead Transarterial Chemoembolization for Treatment in Patients With Liver Cancer

Abstract: This study aimed to investigate the clinical response and short-term survival and further explore the comprehensive factors for predicting clinical outcomes in patients with liver cancer treated by drug-eluting beads transarterial chemoembolization . Forty-nine patients with liver cancer who received drug-eluting beads transarterial chemoembolization treatment were consecutively enrolled in this cohort study. Demographic features, medical histories, clinicopathological properties, biochemical indexes, previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
1
10
1
Order By: Relevance
“…Considering that CSM is the first drug‐eluting beads product in China, more comprehensive studies investigating the efficacy of DEB‐TACE with CSM in Chinese patients are needed. In this present study, we found that DEB‐TACE with CSM achieved CR rate of 37.9% and ORR rate of 81.8% in HCC patients, and CR in our study was numerically higher compared with the previous studies, which might due to: (a) the beads used in the DEB‐TACE procedures varied among studies, which might result in different treatment responses, such as, in a previous study they used DcBeads ® in the DEB‐TACE procedure; (b) the criteria that used to assess treatment responses were different among studies, which led to differentiate CR rates; for example, a previous study used mRECIST criteria and European Association for the Study of the Liver (EASL) criteria, while only mRECIST criteria was used in our study; (c) histological types of liver cancers were inconsistent among studies, and thereby, different CR rates were observed; for instance, a previous study enrolled HCC patients, primary intrahepatic cholangiocarcinoma patients, and secondary liver cancer patients, while only HCC patients were included in our study; (d) skills of surgeons might be different among these studies, thereby leading to different CR rates. As to survival profiles, there are some previous studies investigate OS in liver cancer patients treated by DEB‐TACE; for example, median OS treated by DEB‐TACE with DcBeads ® in a study is 369 days (95% CI: 310‐589 days), and another study shows that mean OS in liver cancer patients treated by DEB‐TACE with CSM is 384 days (95% CI 373‐395 days) .…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Considering that CSM is the first drug‐eluting beads product in China, more comprehensive studies investigating the efficacy of DEB‐TACE with CSM in Chinese patients are needed. In this present study, we found that DEB‐TACE with CSM achieved CR rate of 37.9% and ORR rate of 81.8% in HCC patients, and CR in our study was numerically higher compared with the previous studies, which might due to: (a) the beads used in the DEB‐TACE procedures varied among studies, which might result in different treatment responses, such as, in a previous study they used DcBeads ® in the DEB‐TACE procedure; (b) the criteria that used to assess treatment responses were different among studies, which led to differentiate CR rates; for example, a previous study used mRECIST criteria and European Association for the Study of the Liver (EASL) criteria, while only mRECIST criteria was used in our study; (c) histological types of liver cancers were inconsistent among studies, and thereby, different CR rates were observed; for instance, a previous study enrolled HCC patients, primary intrahepatic cholangiocarcinoma patients, and secondary liver cancer patients, while only HCC patients were included in our study; (d) skills of surgeons might be different among these studies, thereby leading to different CR rates. As to survival profiles, there are some previous studies investigate OS in liver cancer patients treated by DEB‐TACE; for example, median OS treated by DEB‐TACE with DcBeads ® in a study is 369 days (95% CI: 310‐589 days), and another study shows that mean OS in liver cancer patients treated by DEB‐TACE with CSM is 384 days (95% CI 373‐395 days) .…”
Section: Discussioncontrasting
confidence: 55%
“…Drug‐eluting beads‐transarterial chemoembolization is designed with drug‐loaded microspheres, and it is able to realize a favorable pharmacokinetic profile: The release of cytotoxic agents is in a sustained manner, which enhances the intratumoral concentration of loaded drugs and reduces the systemic drug‐related toxicity . Some previous studies are carried out to explore the treatment response of DEB‐TACE in liver cancer patients . For instance, a study reveals that DEB‐TACE with DcBeads ® achieves CR of 22% and ORR of 89% in 34 Irish HCC patients .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other factors, such as albumin-bilirubin, platelet-albumin-bilirubin grades, ECOG stage, BCLC stage, portal vein invasion, CA-199, Hb, ALP, ALB and AFP level, have also been proved to predict tumor response and survival. [22][23][24] In this study, abnormal ALP, history ofalcohol intake and largest nodule Notes: Data was presented as median (25th-75th quantiles) or count (%). Comparison between the two groups was determined by Wilcoxon rank sum test.…”
Section: Discussionmentioning
confidence: 99%